Editorial board, information for authors, and other front matter - Lisa Lundy (Journal of Applied Communications, 2009)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 93, no. 3-4 (2009) of Journal of Applied Communications
Keywords: masthead